New combinations and a key to the species of Pelekium (Thuidiaceae) in sub-Saharan Africa and the East African Islands - Phephu, Nonkululo; van Rooy, Jacques; van Wyk, Abraham E. (Phytotaxa, 2013)
Two taxa currently recognised in Thuidium are transferred to Pelekium to complete the relocation of monoicous species from Thuidium subg. Microthuidium to Pelekium. The new combinations are: Pelekium thomeanum (Broth.) Phephu stat. et comb. nov. (basyonym Thuidium involvens (Hedw.) Mitt. var. thomeanum Broth.), now recognised as a species distinct from P. involvens (Hedw.) A. Touw, and P. pseudoinvolvens (Müll. Hal.) Phephu comb. nov. A full taxonomic treatment, including descriptions and notes on the distribution and ecology of these two species is presented, followed by a key to the African species of Pelekium.